Evaluating the Digital Leadership Competence of School Heads from Teachers’ Perspectives: An Exploratory Study - Dacumos, Eloisa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the digital leadership competencies of elementary school heads in Villaverde District, Schools Division of Nueva Vizcaya, as perceived by public elementary school teachers. Guided by established digital leadership frameworks, transformational leadership, instructional leadership, and distributed leadership, the study aimed to assess school heads’ digital leadership competencies, identify their strengths and areas for improvement, and provide interventions to strengthen leadership practices. A descriptive-correlational research design was employed using a structured survey questionnaire supplemented by interviews. The respondents were public elementary school teachers selected through stratified random sampling from the twelve public elementary schools in the district. Descriptive statistics, including frequency, percentage, weighted mean, and standard deviation, were used to analyze the data. The findings revealed that teachers generally perceived the digital leadership competencies of school heads as evident, while digital leadership practices and strengths were rated as very evident. School heads demonstrated strong performance in digital infrastructure development, technology integration, digital communication, innovation, and professional development. However, opportunities for improvement were identified in strengthening teachers’ digital competencies, enhancing communication of digital initiatives, providing continuous technology-related training, promoting inclusive digital environments, and improving data-informed decision-making. The study concludes that effective digital leadership positively contributes to teaching, learning, and school management and recommends continuous professional development, stronger stakeholder engagement, expanded teacher support, and sustained investment in digital resources and infrastructure. This study supports Sustainable Development Goal 4 (Quality Education) by promoting effective educational leadership and technology-enhanced learning, and Sustainable Development Goal 9 (Industry, Innovation and Infrastructure) by encouraging digital innovation and technology integration in schools. The findings contribute to institutional sustainability by providing evidence that supports leadership development, continuous professional growth, and the long-term improvement of digital transformation initiatives in elementary education.